Sexuality, Relationships and Factors Leading to Teenage Pregnancy among Students in Glan – Padidu National High School - Lynn Marie Simporios Infante (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to find out the context of sexuality, relationships and factors leading to teenage pregnancy among students of Glan – Padidu National High School. The researcher used descriptive-quantitative research design. The respondents of the study were nine (9) students who were identified using purposive random sampling method. The data showed that respondents’ parents were mostly elementary level, earning P5,000 below monthly and most were self – employed. As to context of sexuality and relationships, most of the respondents engaged in sex when they were 14 – 16 years old, with partners 20 years old and above. Because of physical attraction, expression of love, and curiosity they engaged in such activity. Various factors lead students to get involve in premarital sex. Home factors such as parents lack of supervision; environmental factor such as TV show, movies and peer pressure; and emotional factor such as to satisfy the sexual needs. With this, it is recommended to create an effective program such as parental seminar, no to teenage pregnancy campaign, true love waits seminar and development of an IEC material to at least lessen the growth of statistics if not totally eliminate pre – marital sex among students at a very early stage.